Financial Sector Assessment Program : Brazil - IAIS Insurance Core Principles - International Monetary Fund; World Bank (World Bank, Washington, DC, 2013)
This report is a full assessment of Brazil's compliance with the Insurance Core Principles (ICPs) of the International Association of Insurance Supervisors (IAIS), as adopted in October 2011. Regulation and supervision of the insurance industry in Brazil is largely the responsibility of the National Council for Private Insurance (CNSP) and the Superintendency of Private Insurance (SUSEP). The assessment is based solely on the laws, regulations, and other supervisory requirements and practices that were in place at the time of assessment. Brazil is one of the first jurisdictions to be assessed under the 2011 version of the ICPs. In the last few years the insurance industry experienced an explosive growth doubling the premium between 2005 and 2010 however, growth potential remains significant. Investments by the insurance sector are conservative and short term, primarily comprising fixed income instruments. Currently around 88 percent of the insurance business is sold by around 70 thousand active brokers, but the supervision and disclosure requirements are thin.